Tuberculous Pyomyositis: A Rare but Serious Diagnosis. (24th March 2013) - Krishnasamy, Vikram; Joseph, Matthew
Abstract : Tuberculous pyomyositis is a rare clinical entity with serious consequences if a diagnosis is not established early. A 53-year-old female with a past medical history of sarcoidosis and pulmonary fibrosis presented from an outside hospital with persistent fevers and a rash. She had been hospitalized multiple times at an outside hospital without any improvement in her symptoms. On examination, she was noted to have a large area of left upper lower extremity (LUE) tenderness with superimposed erythema. Laboratory data revealed a white blood cell count of 22, 300. Computed tomography (CT) scans of the LUE, chest, and left lower extremity (LLE) showed multiple intramuscular abscesses in those regions without evidence of osteomyelitis. Subsequent drainage of the abscesses and resulting cultures revealed Mycobacterium tuberculosis . The patient was started on therapy with rifampin, isoniazid, pyrazinamide, and ethambutol. However, the patient developed hepatitis on these agents and subsequently went into septic shock with multiorgan failure. Care was eventually withdrawn as a result of a poor prognosis. This case illustrates the severe consequences of TB pyomyositis if not diagnosed promptly. While tuberculosis is uncommon in the United States, it should be an important consideration in the differential diagnosis of immunocompromised patients.